Comparative Study of Verdicts of Code of Ethics and Criminal Verdicts against Members of the Police Who Committed Criminal Offense - Ustad, Ahimzar Zulfikar; Marwiah, Siti (Universitas Islam Lamongan, 2023)
Abstract Bripda Randy is a member of the Police who, is together with his girlfriend, aborted the girlfriend's fetus. So that he was processed by the Police code of ethics and criminal law, and a code of ethics verdict was handed down first and then a criminal verdict. However, in this case, there is an inconsistency in the application of the legislation in that the criminal verdict is decided first than the code of ethics. The research aims to analyze the law enforcement of Indonesian National Police members who commit criminal acts based on the code of ethics and criminal law and a comparative study of the code of ethics decisions and criminal decisions. The type of research is normative juridical. The results of this study are that members of the National Police who commit criminal offenses are processed by the code of ethics and the general court. The decision of the Code of Ethics Commission Session Number: PUT KKEP/7/I/2022/KKEP was decided on January 27, 2022. Meanwhile, the Mojokerto District Court Decision Number: 46/Pid.B/2022/PN. Mjk was decided on April 27, 2022. This shows inconsistencies in applying laws and regulations, namely Article 12 paragraph (1) letter an of Government Regulation Number 1, the Year 2003 and Article 21 paragraph (3) letter a of Regulation of the chief of the Indonesian National PoliceNumber 14, the Year 2011. The inconsistency has violated the principle of presumption of innocence; it also has an impact on not achieving the objectives of the law, namely justice, certainty and expediency.Â Â